Pencitraan Budaya Media Televisi Terhadap Penikmatnya - Handriyotopo Handriyotopo (Institut Seni Indonesia Surakarta, 2007)
In audiovisual television image, media culture almost a part of contemporary society life. In the social culture construction the influence of each other culture is so awful. The influence patch on the society so quickly and closely in audience marrow. The culture which is construction and image by television media is for capitalism. The society couldn’t choose the capital owner culture symbol because that just for business. Artistic show culture which has local identity doesn’t attract the capital owner. In Indonesia it’s out of the ring because of television spread phenomenon. It seems only popular and contemporary show that can support these business media. The national culture value which has culture identity disappears by hegemony of global culture. The media beholder couldn’t do anything over by a barrel capitalism media show that fulfilling with consumerisms try to offering image and meaning in a while. Keyword: Media Culture, Image, Television